2014
DOI: 10.1155/2014/702701
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Drug and Antidrug Levels: A Rational Approach in Rheumatoid Arthritis Patients Treated with Biologic Agents Who Experience Inadequate Response While Being on a Stable Biologic Treatment

Abstract: Clinical response in patients with rheumatoid arthritis (RA) treated with biologic agents can be influenced by their pharmacokinetics and immunogenicity. The present study evaluated the concordance between serum drug and antidrug levels as well as the clinical response in RA patients treated with biological agents who experience their first disease exacerbation while being on a stable biologic treatment. 154 RA patients treated with rituximab (RTX), infliximab (IFX), adalimumab (ADL), or etanercept (ETN) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 56 publications
6
34
0
Order By: Relevance
“…Moreover, data on reference TNF inhibitors, such as adalimumab and inflix imab, have already documented that ADAs and resulting drug levels are associated with better clinical responses in patients with RA. 37 This effect is generally accepted for inflammatory bowel diseases, in which patients are dosed according to the trough level of the drug, but this approach is not widely used in rheumatology practice. 38 …”
Section: Effects Of Ada On Drug Efficacymentioning
confidence: 99%
“…Moreover, data on reference TNF inhibitors, such as adalimumab and inflix imab, have already documented that ADAs and resulting drug levels are associated with better clinical responses in patients with RA. 37 This effect is generally accepted for inflammatory bowel diseases, in which patients are dosed according to the trough level of the drug, but this approach is not widely used in rheumatology practice. 38 …”
Section: Effects Of Ada On Drug Efficacymentioning
confidence: 99%
“…In a third of cases such drugs are ineffective and this is due to primary treatment failure (drug inefficacy or serious side effects) or secondary treatment failure (drug loss of efficacy after initial good response). It has been shown that serum levels of ADA, ETN and IFX correlate with the clinical response in RA, while in ankylosing spondylitis (AS) data are controversial [1][2][3][4]. Similarly, anti-drug Ab levels inversely correlate with drugs levels and therapeutic response [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that serum levels of ADA, ETN and IFX correlate with the clinical response in RA, while in ankylosing spondylitis (AS) data are controversial [1][2][3][4]. Similarly, anti-drug Ab levels inversely correlate with drugs levels and therapeutic response [4][5][6]. The mechanism of drug inactivation is linked to anti-drug Ab formation (against biological medications) which causes the neutralization of the drug and its increased clearance [5]: only 4% of patients with anti-adalimumab antibodies (anti-ADA Ab) achieved clinical remission compared to 34% anti-ADA Ab negative patients [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is speculated that this is largely due to induction of immunogenicity where patients develop antiinfliximab antibodies (ATIs) that bind to IFX rendering it ineffective. Therapeutic drug monitoring of the biological active fraction of IFX in patients' serum has shown great promise to improve treatment outcomes in patients suffering from inflammatory autoimmune diseases [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%